The Political Parties and Organizations in Iran During the Years (1905 – 1941) - Delzar Salih Sadiq; Saadi Uthman Haruti (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
At the beginning of the twentieth century, Iran witnessed a sensitive phase of political conflict, as a number of enlightened intellectuals and politicians dedicated their efforts to saving the country from stagnancy and backwardness. In order to convoy with the developments in Europe during that period. At first they tried to forcing the government of the Qajar state (1796-1925) through the press, to carry out the required reform. But when these attempts did not succed, they tried to achieve their goals by establishing political parties and organizations. And the first attempts were to establish secret organizations outside the country, by the Iranians living in the Caucasus regions. This later paved the way for the establishment of political parties and organizations in Iran. These organizations participated in the constitutional revolution (1905-1911), and strongly defended the gains of that revolution. Under these circumstances, specifically during the years (1905-1941), many political parties and organizations that had different ideological trends appeared; Such as: (General Socialists / 1905 - 1909), (Communist Party/ 1920 - 1938) and many other parties. During the aforementioned period, party life in Iran passed through two phases: In the first phase, which includes the years (1905-1921), political parties and organizations were faced some obstacles, despite that, they practiced a clear impact on the political life in that country. As for the second phase, which lasted for years (1921-1941), which is the period of Reza Shah's rule, the Iranian parties and organizations faced more complex obstacles and problems. Because the government tightened the grip around political freedom. As a result, a very limited number of parties have been able to influence the political events in Iran.